2000
DOI: 10.1073/pnas.190177497
|View full text |Cite
|
Sign up to set email alerts
|

An alternative pathway to β-carotene formation in plant chromoplasts discovered by map-based cloning of Beta and old-gold color mutations in tomato

Abstract: Carotenoid pigments in plants fulfill indispensable functions in photosynthesis. Carotenoids that accumulate as secondary metabolites in chromoplasts provide distinct coloration to flowers and fruits. In this work we investigated the genetic mechanisms that regulate accumulation of carotenoids as secondary metabolites during ripening of tomato fruits. We analyzed two mutations that affect fruit pigmentation in tomato (Lycopersicon esculentum): Beta (B), a single dominant gene that increases ␤-carotene in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
489
3
22

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(542 citation statements)
references
References 34 publications
28
489
3
22
Order By: Relevance
“…CCS exhibits lycopene β-cyclase activity 54 and has an orthologous relationship with chromoplast-specific lycopene β-cyclase (CYC-B) 55 , which exhibits ethylene-dependent repression 44 during tomato ripening. CCS expression was extremely high during pepper ripening (Fig.…”
Section: Comparative Fruit Ripeningmentioning
confidence: 99%
“…CCS exhibits lycopene β-cyclase activity 54 and has an orthologous relationship with chromoplast-specific lycopene β-cyclase (CYC-B) 55 , which exhibits ethylene-dependent repression 44 during tomato ripening. CCS expression was extremely high during pepper ripening (Fig.…”
Section: Comparative Fruit Ripeningmentioning
confidence: 99%
“…Reconstitution of the pathway in other crops depends on the metabolic bottleneck, as illustrated by canola, tomato and potato [33][34][35][36][37]. The Grand Challenges in Global Health initiative of the Bill & Melinda Gates Foundation is funding biofortification projects on banana, cassava, and sorghum for Africa.…”
Section: Molecular Breeding and Transgenicsmentioning
confidence: 99%
“…The sequence similarity between the putative wild species CYCB genomic amplicons with the mRNA sequence available on GenBank indicates this gene is intronless. Translation of this sequence and analysis of the predicted polypeptide showed identity to the AF 254793 sequence (Ronen et al, 2000) varying from 95.5% (S. neorickii) to 100% (S. lycopersicum 'Santa Clara'). The results support the specificity of the pair of primers for the CYCB gene sequences, since no other PCR product was obtained in the described assay conditions.…”
mentioning
confidence: 95%
“…Two lycopene beta-cyclases have also been described in tomato; one is LCYB and the other is the chromoplastspecific lycopene beta-cyclase (CYCB) (EC 1.14.-.-). The characterization of two yellow/orange fruit mutants (delta and Beta) revealed that these traits are controlled by distinct lycopene cyclase genes (Ronen et al, 1999(Ronen et al, , 2000. The Beta mutation controls the up regulation of the CYCB gene, so that the fruit accumulates the orange pigment beta-carotene.…”
mentioning
confidence: 99%
See 1 more Smart Citation